Govt needs to scale down BR1M aid, says expert - Hamsawi, Roziana (New Straits Times, 2014)
AID in the form of cash handouts should be minimised if the government is to effectively address the fiscal deficit problem, said academician Dr Irwan Shah Zainal Abidin.